Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Step-by-step explanation:
Given the function, f(x) = -3x + 4, you basically need to choose any input (x-value) and substitute those values into the function.
- f(0) = -3x + 4, where the input is x = 0.
f(0) = -3(0) + 4
f(0) = 0 + 4
f(0) = 4 [this is the value of your final column, in the f(x)].
2. f( 1 ) = -3( 1 ) + 4, where the input is x = 1.
f( 1 ) = -3( 1 ) + 4
f( 1 ) = -3 + 4
f( 1 ) = 1 [this is the value of your final column, in the f(x)].
3. f(2) = -3(2) + 4, where the input is x = 2.
f(2) = -6 + 4
f(2) = -2 [this is the value of your final column, in the f(x)].
All you need to do is plot the following points on your graph:
{(0, 4), (1, 1), (2, -2)}
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.